Effectiveness of Leukocyte Removal by Imugard III - Siripan Kijkornphan (2018)
Study was conducted to evaluate the effectiveness of Imugard III - RC (4B) to remove leukocyte from packed red cells (PRCs). The leukafiltration set, Imugard III (4B), bedside use for PRCs or whole blood was converted to laboratory use by connecting the distal end of filter tubing to the transfer bag and the proximal end of tubing to the primary blood pack by sterile connecting device to ensure that the closed system is intact. Twenty units of PRCs were prepared from CPD whole blood by removal of platelet rich plasma. All units were stored at 4°C for 1 day before filtration. Volumes of PRC/Bag ranged from 240 - 340 ml, mean = 276.75 ml and SD = 26.57. Prefiltration WBC/Bag ranged from 464 × 106 - 5910 × 106 cells, mean = 2862.05 × 106 cells and SD = 1280.87 × 106. The filtration time/Bag ranged from 18-45 min, mean = 27.3 min and SD = 7.9. The WBC removals ranged from 99.99 per cent - 100 per cent, mean = 99.99 per cent and SD = 0. The residual WBC in PRC/Bag ranged from 0 - 0.24 × 106 cells, mean = 0.134 × 106 cells and SD = 0.063 × 106. The RBC loss from PRCs with no additive solution was approximately 15 per cent. There was no need for priming and purging the filtration set with saline before and after filtration. Conclusion : The reduction of WBC by 20 sets of Imugard III-RC (4B) was 99.99 per cent or higher with the residual WBC <1 × 106 which is able to reduce nonhemolytic transfusion reaction, CMV transmission and HLA alloimmunization.